A Recombinant Porcine Reproductive and Respiratory Syndrome Virus Stably Expressing a Gaussia Luciferase for Antiviral Drug Screening Assay and Luciferase-Based Neutralization Assay - Li, Yanhua; Ren, Cicheng; Li, Chenxi; Xiao, Yihong; Zhou, Yanyang (Frontiers in Microbiology, 2022)
The reverse genetics system is a valuable tool in the virological study of RNA viruses. With the availability of reverse genetics, the porcine reproductive and respiratory syndrome virus (PRRSV) has been utilized as a viral vector for the expression of foreign genes of interest. Here, we constructed a full-length cDNA clone of a high pathogenic PRRSV (HP-PRRSV) TA-12 strain. Using this cDNA clone, we generated a reporter virus expressing a gaussia luciferase (Gluc) via an additional subgenomic RNA between ORF7 and 3’UTR. This reporter virus exhibited similar growth kinetics to the wild-type (WT) virus and remained genetically stable for at least 10 passages in MARC-145 cells. In cells infected with this reporter virus, the correlation between the expression levels of Gluc in culture media and the virus titers suggested that Gluc is a good indicator of the reporter virus infection. With this reporter virus, we further established the Gluc readout-based assays for antiviral drug screening and serum neutralizing antibody detection that exhibited comparable performance to the classical assays. Taken together, we established a reverse genetics system of HP-PRRSV and generated a novel reporter virus that could serve as a valuable tool for antiviral drug screening and serum neutralizing antibody detection.